Learning Arabic in Heterogeneous Classrooms: Experiences of Non-pesantren Students in Indonesian Islamic Higher Education - Adittia Batalipu; Mukhtar I Miolo; Suharia Sarif (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
This study explores the lived learning experiences of non-pesantren students in Arabic language learning alongside pesantren students at IAIN Sultan Amai Gorontalo. Although previous studies have examined learning difficulties and competency disparities in Arabic language learning, limited attention has been paid to how non-pesantren students interpret their socio-academic experiences in heterogeneous classrooms. Employing a qualitative phenomenological approach, this study involved 20 non-pesantren students. Data were collected through reflective forms and semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that differences in educational background create initial competency gaps that shape students’ psychological and socio-academic experiences. Non-pesantren students initially experienced anxiety and low self-confidence; however, these challenges also fostered motivation and academic adaptation. Interaction with pesantren peers functioned as academic support through collaborative learning and peer assistance. Students also developed self-regulated learning strategies by utilizing digital resources and peer discussions. The study contributes to Arabic language learning research by demonstrating that heterogeneous classrooms function as spaces for academic identity negotiation, peer-mediated adaptation, and learner agency. Therefore, inclusive instructional management is needed to accommodate students from diverse educational backgrounds.